(x-2/x+2)+(4/x+2)+4=0

Simple and best practice solution for (x-2/x+2)+(4/x+2)+4=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (x-2/x+2)+(4/x+2)+4=0 equation:


D( x )

x = 0

x = 0

x = 0

x in (-oo:0) U (0:+oo)

x-(2/x)+4/x+2+2+4 = 0

x-2*x^-1+4/x+2+2+4 = 0

1*x^1+2*x^-1+8*x^0 = 0

(1*x^2+8*x^1+2*x^0)/(x^1) = 0 // * x^2

x^1*(1*x^2+8*x^1+2*x^0) = 0

x^1

x^2+8*x+2 = 0

x^2+8*x+2 = 0

DELTA = 8^2-(1*2*4)

DELTA = 56

DELTA > 0

x = (56^(1/2)-8)/(1*2) or x = (-56^(1/2)-8)/(1*2)

x = (2*14^(1/2)-8)/2 or x = (-2*14^(1/2)-8)/2

x in { (-2*14^(1/2)-8)/2, (2*14^(1/2)-8)/2}

x in { (-2*14^(1/2)-8)/2, (2*14^(1/2)-8)/2 }

See similar equations:

| (13x-180)+(6x+17)+67=180 | | 82=2(1-5x) | | 4(x+5)-4=33 | | 10+x-1/3x=0 | | 4(x+5)-4=48 | | 8(g+4)=72 | | 6x-(4x+8)=10 | | 3x-2(x-2)+x= | | -4(x-3)=5(2x-6) | | 18=4(y+2)+2 | | 6(x-1)=24 | | x^2+x-252=0 | | 6+8/3=-14 | | 2(3)-7= | | 2a-7= | | 4x-2+6y+y-4= | | -10=-12+4/7n | | -3x=3/4 | | 3(r+3)=6 | | (180-13x)+(6x+17)+67=180 | | 7(k+3)+5=-5(k-3)+17 | | 2/3+x=-13/3 | | 1000=232+2c | | -18=m/8 | | 111-10g=11 | | -2y=24 | | 11-10g=11 | | 9x-9+6x+6=360 | | 28+27k=946 | | y-25=34 | | 2x+4=7x-26 | | 13-7s=20 |

Equations solver categories